Transformational Leadership of School Administrators Affecting the Performance of Teachers under the Office of the Secondary Education Service Area Office Chachoengsao - การเนตร, ชนกนันท์; แก้วมงคล, ทรงยศ (การประชุมวิชาการระดับชาติและนานาชาติ เบญจมิตรวิชาการ ครั้งที่ 16, 2026)
This research investigated school administrators and teachers under the Secondary Educational Service Area Office Chachoengsao. The objectives were to examine 1) the transformational leadership of school administrators 2) teachers performance; 3) the relationship between administrators’ transformational leadership and teachers performance and 4) the impact of administrators’ transformational leadership on teachers performance. The research sample consisted of 298 school administrators and teachers, determined using the Krejcie & Morgan table. The research instrument was a 5-point Likert scale questionnaire, which yielded an Index of Item-Objective Congruence (IOC) between .60-1.00 and a reliability coefficient of .939. Data were analyzed using frequency, percentage, mean, and standard deviation. Hypotheses were tested using Pearson’s Product-Moment Correlation and Stepwise Multiple Regression Analysis.          The research findings revealed that: 1. The overall transformational leadership of school administrators was at a high level. 2. The overall teacher performance was at a high level. 3. The relationship between the transformational leadership of school administrators and teacher performance was at a high level (r = .747) with statistical significance at the .01 level. 4. Transformational leadership significantly affected teacher performance. The aspect with the highest impact was Individualized Consideration (b = .728) at a .01 level of significance. The multiple correlation coefficient (R) was .888, indicating that the predictor variables could collectively explain 78.60% of the variance in teacher performance.